2021
DOI: 10.1007/s12011-021-02997-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Selenium Deficiency: a Systematic Review

Abstract: Several studies have indicated that selenium deficiency may be detrimental in the context of various viral disorders, and in the case of COVID-19, several studies have reported heterogeneous results concerning the association of selenium deficiency with the severity of disease. To summarize the available data surrounding the association of body selenium levels with the outcomes of COVID-19, a systematic search was performed in the Medline database (PubMed), Scopus, Cochrane Library, Embase, and Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 54 publications
5
62
0
1
Order By: Relevance
“…Fernández-Lázaro et al [ 62 ] found that no significant effects were observed in myosin heavy chain expression in muscle tissue after oral selenium supplementation with 180 µg/day or 240 µg/day in the form of selenomethionine or with 200 µg/day in the form of sodium selenite, although the changes in protein expression observed in their study might have been different if the analysis was done on heart tissues only, as in the present study. Gene ontology enrichment analysis performed for the identified differentially-expressed proteins ( Figure 2 ) indicated biological processes including plasma membrane repair, muscle structure development, and cytoskeleton organization, which confirms the positive effects of a diet enriched in Se on body function reported in several previous studies [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The cytoskeleton has been indicated as a biological process in functional annotation analysis of differentially expressed genes as a result of high dietary selenium supplementation in sheep reported by Elgendy et al [ 72 ].as.…”
Section: Discussionsupporting
confidence: 83%
“…Fernández-Lázaro et al [ 62 ] found that no significant effects were observed in myosin heavy chain expression in muscle tissue after oral selenium supplementation with 180 µg/day or 240 µg/day in the form of selenomethionine or with 200 µg/day in the form of sodium selenite, although the changes in protein expression observed in their study might have been different if the analysis was done on heart tissues only, as in the present study. Gene ontology enrichment analysis performed for the identified differentially-expressed proteins ( Figure 2 ) indicated biological processes including plasma membrane repair, muscle structure development, and cytoskeleton organization, which confirms the positive effects of a diet enriched in Se on body function reported in several previous studies [ 15 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. The cytoskeleton has been indicated as a biological process in functional annotation analysis of differentially expressed genes as a result of high dietary selenium supplementation in sheep reported by Elgendy et al [ 72 ].as.…”
Section: Discussionsupporting
confidence: 83%
“…The results indicate that these metal levels are altered in a severity-dependent manner, showing that trace elements place a major role in COVID-19 pathology. Many recent reviews have commented that trace elements, vitamins and heavy metals play a major role in the pathophysiology of COVID-19 due to their pivotal role in homeostasis of the immune and other major systems of the body [22][23][24][25]. In vitro studies showed that SARS-CoV-2 viral spike protein interacts with ACE2 receptor, which is a zinc-dependent peptidyl dipeptide hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review including a total of 11 studies, nine of them suggested lower blood Se levels associated with worse outcomes, although the other two studies found no significant association between Se and COVID-19 [ 105 ]. In one of the included studies, urinary Se level was higher in severe and fatal cases compared with nonsevere and recovered patients.…”
Section: Role Of Selenium In Covid-19: Clinical Significance and Impl...mentioning
confidence: 99%
“…In one of the included studies, urinary Se level was higher in severe and fatal cases compared with nonsevere and recovered patients. Overall, Se deficiency was thus generally associated with worse outcomes, and COVID-19 patients exhibited Se levels lower than healthy subjects [ 105 ].…”
Section: Role Of Selenium In Covid-19: Clinical Significance and Impl...mentioning
confidence: 99%